DEVELOPING A MODEL OF SMART SCHOOL CANTEEN: AN INTRODUCTION OF SELF-PURCHASING TECHNOLOGY - Zainal, Andri; Sriwedari, Tuti; Harahap, Khairunnisa; Suhariyanto, Joko (Journal of Community Research and Service, 2018)
AbstractIn general, the development of character building in a formal education can be applied through buying and selling transaction activities in the school canteen. The widespread use of computer technology can also be applied in trade activities in school canteens as an effort to establish the character of Indonesia's young generation with integrity and honesty. The introductory on the use of technology through a Self-Purchasing System or also commonly known as the Self-Check-out System is a mechanism that provides an opportunity for customers to process their purchases by scanning the items they buy and making direct payments before leaving the store/store. This technology can be initiated into religious and non-religious-based elementary schools that practice the values integrity and honest character from a specific religion to general values. However, even though these values have become a daily part of learning, the use of modern technology in the practice of education cannot be denied. Thus, the combination of pedagogy on the conceptual character-building value in the classroom and the use of science and technology in trading activities in the school canteen will accelerate the formation of integrity and honest character within the pupils.Keywords: Character Building, Self-Purchasing System, Governance, Smart School Canteen Model.